Local complications and lymphadenitis after BCG–M vaccination in children – сhoosing the right tactics - M. E. Lozovskaja; G. A. Stepanov; Yu. A. Yarovaya; A. V. Mosina; M. A. Osipova; O. P. Zakharova (Журнал инфектологии)
Тhe aim: to analyze the cases of complications of BCGvaccination in children, potential risk factors, patient management tactics.Materials and methods: The statistical data on local complications of BCG-M vaccination in Saint Petersburg (Russia) from 2012 to 2019 was studied. To verify the diagnosis of post-vaccinal complication the Mantoux test, diaskintest or QuantiFERON-TB, X-ray examination, morphological and bacteriological examination were used in cases of indication. Observations of 22 children aged from 1,5 months to 1,5 years with complications after vaccination with BCG-M were analyzed.Results. Since 2010, the sparing BCG-M vaccine has been used in St. Petersburg for primary immunization. The incidence of local complications over the past 8 years was 0,002% – 0,012% of the number of vaccinated children. A cold abscess was diagnosed in 11 (50,0%), BCG-lymphadenitis in 9 (40,9%), an ulcer in 2 (9,1%) children. In 14 (63,6%) of 22 children complications of vaccination were detected in the phase of abscess formation. Fore children underwent surgery with diagnoses of nonspecific lymphadenitis (3), soft tissue abscess (1). In these cases, diagnoses of BCG-M complications was established only after morphological examination of the surgical material. In children with complications while the results of Mantoux test were positive, results of diaskintest and QuantiFERON-TB were negative. The detection of Mycobacterium bovis BCG was possible in 5 patients by culture and polymerase chain reaction methods. 2 clinical cases are given.Conclusion: It is necessary to increase the knowledge of pediatricians, pediatric surgeons, nurses of BCG vaccination techniques, diagnosis and treatment of post-vaccination complication, indications for dispensary observation.